Empirical study on the directors and auditors perception relating to the demand for reporting on internal control / Zulkifflee Mohamed - Mohamed, Zulkifflee (2001)
The purpose of this study is to analyse the demand for reporting on internal control. For the purpose of this study two financial statement user groups (auditors and directors) were identified and surveyed to determine whether they agreed on the matters that: (1) Management Reports on Internal Control (MRIC) are useful; (2) Management Reports on Internal Control influence decision making and (3) Management Reports on Internal Control improves overall financial reporting in Malaysia. In addition, this research also examine whether responses varied when based on user group. The results indicate that auditors and directors agreed that internal controls are important. Respondents agreed that voluntary MRICs improve controls and provide additional information for decision-making. Respondents also agreed that mandatory MRICs improved controls but did not agree about MRICs provided additional information for decision-making. The results from the study also indicate that directors were less likely to agree on the importance of MRICs than auditors. Based on the result of this study, it reveals that MRICs do not improved overall financial reporting in Malaysia.